Association among blood pressure, antihypertensive drugs, and amyotrophic lateral sclerosis - Li, Zhiguang; Li, Yan; Zhao, Jiankai; Zhang, Feifei; Dang, Wei; Jia, Yanan; Guo, Fei; Guo, Lixin (Arquivos de Neuro-Psiquiatria, 2025)
Background Amyotrophic lateral sclerosis (ALS) is a fatal and incurable neurodegenerative disease. The impacts of antihypertensive drugs and blood pressure (BP) on ALS are currently debatable.Objective To evaluate the causal relationship involving antihypertensive drugs, BP, and ALS through a Mendelian randomization (MR) analysis.Methods The causal relationship between BP and ALS was evaluated by a bidirectional two-sample MR analysis. Then, a sensitivity analysis was performed using a secondary BP genome-wide association study. The drug-target MR was employed to evaluate the impact of antihypertensive drugs on ALS. Furthermore, we used cis-expression quantitative trait loci (cis-eQTLs) data from brain tissue and blood to validate the positive results by a summary-based MR method.Results We found that an increment in systolic BP (SBP) could elevate the risk of ALS (inverse-variance weighted [IVW] odds ratio [OR] = 1.003; 95% confidence interval [95%CI]: 1.001–1.006; per 10-mmHg increment) and ALS might be protected by angiotensin-converting enzyme inhibitors (ACEIs; OR = 0.970; 95%CI: 0.956–0.984; p = 1.96 × 10−5; per 10-mmHg decrement). A causal relationship was not observed between diastolic BP and other antihypertensive drugs in ALS.Conclusion In the present study, genetic support for elevated SBP serves as a risk factor for ALS. Besides, ACEIs hold promise as a candidate for ALS.
Keywords: Blood Pressure; Antihypertensive Agents; Mendelian Randomization Analysis; Amyotrophic Lateral Sclerosis